PEMBANGUNAN ZONA INTEGRITAS MELALUI SURVEI PERSEPSI ANTI KORUPSI (SPAK) DAN SURVEI PENINGKATAN KUALITAS PELAYANAN (SPKP) DI KOMISI PEMILIHAN UMUM KABUPATEN SUMEDANG - Robby Yulianto (JRPA - Journal of Regional Public Administration, 2026)
The development of an Integrity Zone is a strategic component of bureaucratic reform aimed at establishing government institutions that are transparent, accountable, service-oriented, and free from corrupt practices. For the General Election Commission (KPU) of Sumedang Regency, institutional integrity and public service quality are particularly important because public trust is fundamental to credible and democratic electoral administration. This study aims to describe the development of the Integrity Zone at the KPU of Sumedang Regency by measuring users’ perceptions through the Anti-Corruption Perception Survey (SPAK) and the Service Quality Perception Survey (SPKP). The study employed a survey method with a quantitative descriptive approach. Respondents were selected using purposive sampling based on their direct experience with services provided by the KPU of Sumedang Regency. Data were collected from 76 respondents through an online questionnaire using a six-point perception scale and analyzed using descriptive statistics. The scores were subsequently converted into a four-point scale to determine the Anti-Corruption Perception Index (IPAK) and the Service Quality Perception Index (IPKP). The results show that the IPKP reached 3.80, equivalent to 94.95%, and was classified as Excellent (Grade A). The highest-rated service element was the conformity of service fees with established regulations, with a score of 3.87. Meanwhile, the availability of service information, clarity of service requirements, and convenience of facilities or online service systems received the lowest score of 3.75, although they remained in the Excellent category. The IPAK reached 3.85, equivalent to 96.15%, and was also classified as Excellent (Grade A). The absence of illegal charges received the highest score of 3.87, while non-discriminatory services and the absence of unofficial intermediaries received the lowest score of 3.83. The study concludes that the KPU of Sumedang Regency has demonstrated excellent performance in public service quality and corruption prevention. Nevertheless, continuous improvements are required, particularly in service information, accessibility of facilities and digital systems, equal treatment of service users, and prevention of unofficial intermediaries, to ensure the sustainable development of the Integrity Zone.